The Influence of Self Concept and Self Regulation on Student Learning Outcomes in the Tahfizh Al Qur'an Program at SMA-IT - Firdaus, Febrio; Risnawati, Risnawati; Afandi, Muslim (AR-RASYID : Jurnal Pendidikan Agama Islam, 2024)
In the learning process, students' self-concept and self-regulation will influence the quality of their learning and will determine what their learning outcomes will be like. These two components will apply in any field of study, including the field of tahfizh al-Qur'an. Therefore, this research aims to determine the influence of self-concept and self-regulation on learning outcomes in the tahfizh al-Qur'an program at SMA IT. The type of research used is multiple linear regression research with a quantitative approach. The population was 242 students and the sample was 23 students. Data collection techniques use questionnaires and documentation. The results of this research show that; Self-concept has a significant effect on student learning outcomes in the tahfizh al-Qur'an program, with a significance value of 0.029 0.05. Self-regulation does not have a significant effect on student learning outcome variables, with a significance value of 0.836 0.05. However, self-concept and self-regulation simultaneously appear to have a significant effect on student learning outcomes in the tahfizh al-Qur'an program. The significance value was found to be smaller than 0.05 and the contribution was 50.4%. Therefore, this research concludes that self-concept and self-regulation influence student learning outcomes in the Tahfizh Al-Qur'an program, contributing 50.4%.